PERAN ESTROGEN PADA REMODELING TULANG - Sihombing, Iknes; Wangko, Sunny; Kalangi, Sonny J.R. (JURNAL BIOMEDIK : JBM, 2012)
Abstract: Bone tissues experience continual regeneration of their extracellular components by overhauling the old components. This process is called bone remodeling, which involves several kinds of bone cells. The most important bone cells related to the bone remodeling are osteoblasts, osteocytes, and osteoclats. The bone remodeling is influenced by estrogen. This hormone inhibits bone resorption, resulting in slowing down the osteoporosis process. This antiresorptive effect can be provided also by the estrogen action on osteoblasts, which indirectly influences osteoclast activities. Estrogen has been proved to slow down the decrease of bone mass and fracture risks in women with osteoporosis. Hormone replacement therapy, aimed at replacing estrogen deficiency, consists of phytoestrogen and progesteron; besides that, calcium and vitamine D are needed, too. Keywords: estrogen, bone remodeling, osteoblast, osteocyte, osteoclast.     Abstrak: Tulang merupakan jaringan yang terus menerus melakukan regenerasi komponen-komponen ekstrasel dengan cara menghancurkan komponen tulang yang sudah tua dan menggantikannya dengan yang baru. Proses ini disebut remodeling tulang, yang melibatkan kerja sel-sel tulang tertentu. Sel-sel dalam tulang yang terutama berhubungan dengan pembentukan dan resorpsi tulang ialah osteoblas, osteosit, dan osteoklas. Remodeling tulang dipengaruhi oleh hormon estrogen. Hormon ini menekan resorpsi tulang sehingga dapat menghambat proses kerapuhan tulang. Efek antiresorptif tersebut dapat pula dihasilkan melalui kerjanya pada osteoblas, yang secara tidak langsung mempengaruhi aktivitas osteoklas. Estrogen terbukti dapat mengurangi laju penurunan massa tulang dan risiko fraktur pada wanita dengan osteoporosis. Terapi sulih hormon yang digunakan untuk mengganti defisisensi estrogen ialah fitoestrogen, progesteron, selain itu juga kalsium dan vitamin D. Kata kunci: estrogen, remodeling tulang, osteoblas, osteosit, osteoklas.